Cosmopolitan Spaces in urban Africa. Newly-Created Sociability Places and Social Interactions between Locals and Foreigners - (:unkn) unknown (My University, 2019)
As the famous Nigerian-American writer Chimamanda Ngozi Adichie mentions it in her interviews, “Africa” and “cosmopolitan” are too often considered as opposite. Far from being apart of the World as they are often considered in a patronising outlook, African Cities are fully actors of the changes and are also places of modernity. The paper will focus on the ways cities in Sub-Saharan Africa are dynamic, opened to worldwide influences and circulations such as people coming from all over the World, and especially from Southern countries, ideas or artefacts (for example in food practices, architecture or as graphic or visual arts). The new concept of an “African Cosmopolitan Archipelago” is proposed and discussed. In particular the intense development of the international migrations is a key theme: how do these foreigners settle in the cities, how do they live and which sociability places they create, hence contributing to everyday urban life and sociability (in particular many Chinese people are concerned). In such places we can observe cosmopolitan practices and representations. Newly-created sociability places are not only aimed at welcoming an ethnic community clientèle, but also are turned towards local city dwellers. Foreign restaurants, casinos, new old-styled colonial bars, etc. attract both foreigners and locals, who appreciate the exotic ambiance. These new sociability places are called “creolised” in the way that new forms of cultural exchange develop. Although the desire to modernity and openness to the world do not prevent from identity tensions in the same time. The two main cities studied are Antananarivo in Madagascar and Maputo in Mozambique.
Keywords: African Research